The Crime of the Forced Abortion (The culpability of foeticide in the first quarter of twentieth century) - Lucie Bendová Bednářová (Journal on European History of Law)
This article explores the historical context and legal perspectives surrounding the crime of Forced Abortion in the early 20th century, particularly focusing on cases heard by the Olomouc Regional Court in Czechoslovakia. The analysis of four specific cases highlights the varying outcomes and punishments imposed on individuals involved in forced abortions. The court's approach ranged from acquittal to conviction, taking into account expert testimonies, mitigating circumstances, and the perceived social and moral implications of the crime. The article also examines the evolving views on abortion within society, including discussions on culpability, population interests, and the rights of women. Efforts for legal reform emerged, but ultimately, the strict criminal provisions of the time remained intact.